ANALISIS PERBANDINGAN DEBIT PADA DAS CIMANUK-COPONG KABUPATEN GARUT AKIBAT PERUBAHAN TATA GUNA LAHAN - Mardianti, Fira; Permana, Sulwan (Prodi Sarjana Teknik Sipil, FT, Universitas Tarumanagara, 2024)
The transformation of land into cities to meet the needs of urban infrastructure is happening fast. As a result, the hydrological pattern changes, such as land that previously absorbed water slowly becomes less able to absorb water. The area of the Cimanuk-Copong watershed is 469.11 km^2. Comparative analysis of discharge in the Cimanuk-Copong watershed due to changes in land use is the key to identifying changes in river flow and their impact on the environment using the NRECA (National Rural Electric Cooperative Association) model, then the results of this calculation are calibrated. The results of the analysis of the comparison value of the average flow rate in the past (2003-2012) were 9.23 m^3/s, while the present (2013-2021) is 19.81 m^3/s. The results of the calibration of the efficiency coefficient value of the Nash-Sutcliffe (NSE) model of the Cimanuk-Copong DAS are 0.61663 including 0.36<NSE<0.75 (Qualified). The results of the flow rate calibration will be a strong basis in validating the model used in the field. In 2011, the KRS value obtained was 4.00, while in 2019, the KRS value increased to 5.71. These two KRS values are included in the good category according to the DAS Criteria and Indicators. Even so, changes in increase during this period still indicate a decrease in the condition of the watershed. The Cimanuk-Copong watershed is dominated by three main categories where these categories include farmland with an area of 12162.86 ha, paddy fields with an area of 6596.237 ha, and residential areas with an area of 5587.949 ha. Abstrak Transformasi lahan untuk memenuhi kebutuhan infrastruktur terjadi dengan cepat. Akibatnya, pola hidrologi berubah menjadi kurang dapat meresap air. Analisis perbandingan debit pada DAS Cimanuk-Copong akibat perubahan tata guna lahan menjadi kunci untuk mengidentifikasi perubahan aliran sungai dengan menggunakan model NRECA. Model penelitian berupa perbandingan debit aliran akibat perubahan tata guna lahan DAS Cimanuk-Copong Garut. Hasil nilai perbandingan debit aliran rata-rata tahun 2011-2015 yaitu 12,48 m3/det sedangkan tahun 2015-2019 yaitu 18,91 m3 /det. Hasil kalibrasi nilai koefisien efisiensi model Nash-Sutcliffe (NSE) DAS Cimanuk-Copong yaitu 0,56514 ter.masuk 0,36<NSE<0,75 (Qualified). Hasil kalibrasi debit aliran akan menjadi dasar kuat dalam memvalidasi model yang digunakan sesuai di lapangan. Pada tahun 2011, nilai KRS diperoleh adalah 6,16, sedangkan pada tahun 2019, nilai KRS meningkat menjadi 6,30. Kedua nilai KRS termasuk dalam kategori baik menurut Kriteria dan Indikator DAS. Perubahan peningkatan selama periode tersebut mengindikasikan penurunan kondisi DAS. Perubahan tata guna lahan pada DAS Cimanuk-Copong meliputi area permukiman bertambah 4%, bangunan 1960%, hutan bertambah 43%, pada rumput berkurang 26%, pengisi area air berkurang 33%, perkebunan bertambah 17%, sawah irigasi berkurang 9%, sawah tadah hujan berkurang 3%, semak belukar berkurang 43%, dan tanah ladang berkurang 3%. Hasil penelitian menunjukkan bahwa pengaruh perubahan tata guna lahan berpengaruh terhadap debit aliran.